Quelques-unes des préoccupations comptables actuelles de l’entreprise privée - Castonguay, Claude (Assurances)

(untitled) (HEC Montréal, 1988)
We would like to thank Mr. Claude Castonguay for allowing us to publish this article and Mr. Yves-Aubert Côté, who occupies the chair of Accounting Sciences at l’École des Hautes Études Commerciales. Mr. Côté asked two speakers, one from the public sector, Mr. Rhéal Chatelain, F.C.A., Auditor General of Quebec, and another from the private sector, Mr. Claude Castonguay, Chairman of the Board and Chief Executive Officer of The Laurentian Group, to express their views on the theme: Our choices as a society and accounting research : the outlook for the future. ln his article, Mr. Castonguay covers four basic points : 1. The role of the accounting profession as regards regulatory bodies. 2. International accounting. 3. Accounting in face of the development of new financial tools. 4. Evaluating a company and the forecast for the future. Mr. Castonguay provides thought-provoking and concrete channels to be explored by companies which operate in several provinces or abroad.